(untitled) (Journal of Economic Research & Business Administration, 2016)
The paper discusses the current problems of the transition to international standards of quality based incentive programs, which aim to ensure sustainable development of the competitiveness of Kazakh enterprises both domestically and abroad. The international standardization is one of the most important elements of modern mechanism of quality control. The motivation system in the Republic of Kazakhstan companies should be harmonized with international, regional and national systems and incentives to ensure the interests of the staff in terms of quality and range of products, services and processes, their safety for human life and health, and so on.